USING RIPPLE TECHNIQUE TO IMPROVE THE HORTATORY TEXT WRITING SKILL OF THE ELEVENTH GRADERS OF SMA NEGERI 1 MAGELANG - Sari_ Yunita (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2018)
Writing is one of the four skills in English which should be mastered by students of senior high school. However, students in the eleventh grade of SMA Negeri 1 Magelang find difficulties in writing hortatory text. It is proved from the average score of writing skill (71) which does not reach the standard minimum score for English yet which is 78. Students’ difficulties in learning writing are because of many factors. One of them is teaching technique. Therefore, the writer conducted a study to overcome the problem by applying Ripple Technique. There are two main objectives in this study. The first is to know whether the use of Ripple Technique can increase the students’ hortatory text learning motivation. The second is to know how great the improvement of the students hortatory text writing skill after being taught by using Ripple Technique.The writer conducted a classroom action research (CAR). It was divided into Pre-Cycle, Cycle I, and Cycle II. Furthermore, the writer collected the data using non test (observation, questionnaire, and documentation) and test. The writer selected the eleventh graders of SMA Negeri 1 Magelang, XI IPA 6 as subject of the study. There are 24 students in the class which consists of 15 females and 9 males.Based on the result, there was an improvement of students’ learning motivation in writing hortatory text. The writer’s observation and questionnaire showed that most of the students had behavioral change. It was proved from the result of the writer’s observation and questionnaire that increased. Beside, the improvement also showed from the test results. In Pre-Cycle test, the average score test was 71.96 which belong to good category. In Cycle I test, the average score was 78.63 which belong to good category while In Cycle II test, the average score was 82.17 which belong to good category. The improvement from Pre-Cycle test to Cycle II was 10.21 points.The writer concluded that the Ripple Technique could increase the hortatory text students’ learning motivation. In addition, it also improved the hortatory text writing skill of the eleventh graders of SMA Negeri 1 Magelang in the school year 2017/2018. In brief, this technique help the students to build a background knowledge about the topic which they write in their text and gain more information to be developed. This technique is also interesting for the students to be more active in the learning process.